Question #0e8af

2 Answers
Nov 22, 2017

(sec^2theta-1)cos^2theta=sec^2thetacos^2theta-cos^2theta=1-cos^2theta,(sec2θ1)cos2θ=sec2θcos2θcos2θ=1cos2θ,
=sin^2theta.=sin2θ.

Nov 22, 2017

sin^2 thetasin2θ

Explanation:

The identity is incomplete as its equivalent part has not been mentioned.
Anyway, the given expression can be simplified as follows:

Using the standard identity sec^2 theta -1= tan^2 thetasec2θ1=tan2θ, the given expression becomes tan^2 theta* cos^2 thetatan2θcos2θ

(sin^2 theta)/ (cos^2 thetasin2θcos2θ * cos^2 thetacos2θ

= sin^2 thetasin2θ